FERTILITY VARIATION AND EFFECTIVE POPULATION SIZE IN A TEAK CLONAL SEED ORCHARD - Sumardi Sumardi (Indonesian Journal of Forestry Research, 2011)
A 27 year old  clonal seed orchard of teak (Tectona grandis L.f ) in Padangan, East Java comprising 24 clones, was evaluated for fertility, offspring diversity, and genetic drift. Flower and fruit productions were used to assess clone fertility in the orchard. Fertility variation measured as ‘sibling coefficient’ was found to be 1,62, having high genetic diversity (0,97) and low coancestry (0,03). The clones varied in fertility in which,  25 % of the most fertile clones in the orchard contributed to 47,5 % of flower and fruit yields. Effective population size in the orchard was 15, indicating that 15 of the clones contributed effectively to seed yield. Separating on the amounts of seeds that can be collected, individual collection, and proportional mixing of seed per clone might be useful in restricting over representation of highly reproductive clones thereby increasing genetic diversity in the seed crop. Another way to improve seed yield in the orchard is by increasing the effective population size. Thinning or prunning on highly reproductive clones might be useful in increasing effective population size.